Communication—Ultrafast Anodized Titania Nanotube Arrays Loaded with Quantum Dots via Ultrasonic Assistance. (1st January 2016) - Zhang, Guoshun; Cao, Chunbin; Ye, Jian; Hua, Rimao; Cui, Jingbiao
Abstract : Self-aligned and firmly-structured titania nanotube arrays (TNAs) with excellent photoelectric response were fabricated by anodization in tens of seconds. Furthermore, TNAs were decorated with CdS quantum dots by ultrasonic-assisted successive ionic layer adsorption and reaction (U-SILAR) method. The resulted CdS/TNAs hybrid shows higher visible light absorption, stronger photo current and stable structure than those of the sample by traditional SILAR method.